Single-Incision Versus Standard Multiple-Incision Laparoscopic Cholecystectomy: A Meta-analysis of Experimental and Observational Studies. (October 2014) - Tamini, Nicolò; Rota, Matteo; Bolzonaro, Elisa; Nespoli, Luca; Nespoli, Angelo; Valsecchi, Maria Grazia; Gianotti, Luca
Objective . The advantages of single-incision surgery for the treatment of gallstone disease is debated. Previous meta-analyses comparing single-incision laparoscopic cholecystectomy (SILC) and standard laparoscopic multiport cholecystectomy (SLMC) included few and underpowered trials. To overcome this limitation, we performed a meta-analysis of randomized and nonrandomized studies. Methods . A MEDLINE, EMBASE, and Cochrane Library literature search of studies published in and comparing SILC with SLMC was performed. The primary outcome was safety of SILC as measured by the overall rate of postoperative complications and biliary spillage. Feasibility was another primary outcome as measured by the conversion and operative time. Postoperative pain, length of hospital stay, perioperative blood loss, time to return to normal activity, and cosmetic satisfaction were secondary outcomes. Results . We identified 43 studies of which 30 were observational reports and 13 experimental trials, for a total of 7489 patients (2090 SILC and 5389 SLMC). The overall rate of complications was comparable between groups (relative risk [RR] = 1.08; 95% CI = 0.87-1.35; P = .46), as were the rates of biliary spillage (RR = 1.16; 95% CI = 0.73-1.84; P = .53) and conversion rate (RR = 0.88; 95% CI = 0.53-1.46; P = .62). Operative time was in favor of SLMC (weighted mean difference = 0.73; 95% CI = 0.67-0.79; P < .0001). Secondary outcomes favored SILC, but with marginal advantages. Conclusions . SILC is a feasible technique but without any significant advantage over SLMC for relevant end points. Although secondary outcomes favored SILC, the small magnitude of the advantage and the low quality of assessment methods question the clinical significance of these benefits.